Application of Chaos Analyses Methods on East Anatolian Fault Zone Fractures - Kamislioglu, Mirac; Kulahci, Fatih (Amer Inst Physics, 2016)
Nonlinear time series analysis techniques have large application areas on the geoscience and geophysics fields. Modern nonlinear methods are provided considerable evidence for explain seismicity phenomena. In this study nonlinear time series analysis, fractal analysis and spectral analysis have been carried out for researching the chaotic behaviors of release radon gas (Rn-222) concentration occurring during seismic events. Nonlinear time series analysis methods (Lyapunov exponent, Hurst phenomenon, correlation dimension and false nearest neighbor) were applied for East Anatolian Fault Zone (EAFZ) Turkey and its surroundings where there are about 35,136 the radon measurements for each region. In this paper were investigated of Rn-222 behavior which it's used in earthquake prediction studies.
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 23-29, 2015 -- Rhodes, GREECE
Keywords: Earthquake Prediction; Strange Attractors; Lyapunov Exponents; Gas